Confirmatory Factor Analysis of the Components of Psychological Well-Being in the Persian Version of the Ryff Scale Across Different Ethnic Groups of Afghan Families - Ahmadyar, Zarifullah; Heidari, Mahmood; Mazaheri, Mohammad Ali; Mootabi, Fereshteh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to evaluate the validity and reliability of the short form of the Ryff Psychological Well-Being Scale (1989), consisting of 18 items, within the population of Afghan families across four provinces in Afghanistan.Methods: The present research was descriptive and correlational in nature. A total of 320 families, including fathers, mothers, and one child from each family (960 participants in total), participated in this study using convenience sampling. Data were analyzed through confirmatory factor analysis (CFA) using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the statistical packages SmartPLS 4 and SPSS 27.Findings: After obtaining feedback from Afghan university professors and participants, the face validity of the scale was confirmed. The reliability of the scale was assessed using Cronbach's alpha and composite reliability (CR). The reliability coefficients were calculated as 0.79 for fathers, 0.78 for mothers, and 0.78 for children, with CR values at satisfactory levels. Convergent validity was evaluated using the average variance extracted (AVE), and discriminant validity was assessed and confirmed using the Heterotrait-Monotrait (HTMT) ratio. To improve the model and enhance discriminant validity, two items related to the dimensions of Environmental Mastery and Personal Growth were removed. The findings demonstrated that the reliability and validity evaluations of the scales used in this study were statistically sound and reliable.Conclusion: The study concluded that the 18-item version of the Ryff Psychological Well-Being Scale is a valid and reliable instrument for use within the Afghan family population. Therapists in Iran working with Afghan migrants, as well as Afghan therapists residing in Afghanistan, can utilize this tool in their clinical and research settings.